MONITORAMENTO DE FUANA ATROPELADA NAS RODOVIAS NO ENTORNO DO PARQUE NACIONAL DAS EMAS – GO - SANTOS, Leonardo Santiago Brito; SEIXAS, Márcio Cesar; SETTI, Marília Santiago; SOARES, Afrânio José Soriano (ANAIS DO ENIC, 2020)
-